ENHANCEMENT OF CRITICAL THINKING SKILLS VOCATIONAL STUDENTS IN INDONESIA USING PROBLEM-BASED LEARNING-STEM BY E-LEARNING - Farhan Yadi; Herminarto Sofyan; Herman Dwi Surjono (JURNAL PENDIDIKAN TEKNIK MESIN, 2023)
This study aims to develop a problem-based learning model with the Science, Technology, Engineering, and Mathematics (STEM) approach through e-learning in vocational high schools (SMK) to enhance learning outcomes and critical thinking skills of the students of light vehicle electrical maintenance, which is valid, practical, and effective. The design phase began with determining the fundamental philosophy, theoretical background, hypothetical model, and evaluation aspects, while exhaustive tests were conducted to validate the developed system during the development phase. Based on practical testing in four vocational high schools in Indonesia, the developed PBL-STEM e-learning system is considered valid and effective for enhancing the quality of vocational education. The critical thinking skills of experimental class students have increased, both in groups and individually, as indicated by the progressive percentage increase of 38.32%. The application of this model has proven to be effective in enhancing critical thinking, skills.